Processing of Self-concept and Identity in Individuals with Borderline Personality Disorder: Findings from a Content-Analytic Follow-up Study - Koivisto, Maaria; Melartin, Tarja; Lindeman, Sari M. (European Journal for Qualitative Research in Psychotherapy, 2022)
We explored how five individuals with borderline personality disorder (BPD) perceived their self-concept over the 12 months after attending a psychoeducational intervention at a community mental health care centre. In this mixed-methods process–outcome study, subjective experiences of meaningful development gathered via an in-depth interview were explored using content analysis. Symptom change was assessed by the Borderline Personality Disorder Severity Index interview. A total of 221 utterances related to the processing of self-concept and identity were identified. Content analysis yielded five core categories pertaining to self-concept and identity: 1) from extremely negative and fluctuating self-concept to improved self-worth and stability; 2) self as actor: sense of agency; 3) decreased disconnection from and integration into self of emotions and emotional needs; 4) the importance of understanding the origins of the negative self-concept; and 5) challenges to the processing of self-concept and identity. Identity development was hampered by insufficient self-compassion and perception of the diagnosis as an additional stigma. The data highlight the importance in treatment of achieving change in punitive internalizations and judgmental self-talk. The findings also suggest the value of facilitating a sense of agency and contact with emotional experiences.